2008
DOI: 10.5132/jbse.2008.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of the Sea Urchin Arbacia lixula (Echinodermata: Echinoidea) in Toxicity Tests

Abstract: RESUMO O presente trabalho investigou o ouriço Arbacia lixula quanto ao seu tempo de desenvolvimento embrio-larval, tolerância do desenvolvimento em diferentes salinidades e temperaturas da água de manutenção, sua repetitividade diante de substâncias de referência para uso em testes de toxicidade e sua sensibilidade em comparação com outras espécies de ouriços normal-mente utilizadas no Brasil. O desenvolvimento embrionário de A. lixula a 25°C foi rápido, atingindo a fase de larva pluteus em menos de 24 horas,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 6 publications
1
6
1
Order By: Relevance
“…Despite the low number of tests carried out on species of echinodermatas other than L. variegatus, the values obtained are within the range of variation and/or of the same order of magnitude observed by other authors who investigated the sensitivity of A. lixula LAITANO, 2002;MÁXIMO et al, 2008;RESGALLA et al, 2012), E. lucunter (RUMBOLD; SNEDAKER, 1997; RESGALLA JÚNIOR; LAITANO, 2002) and the sand dollar Mellita quinquiesperforata (LAITANO et al, 2008), which validate the results obtained in this work. On the basis of this, it was suggested that the different species tested have similar sensitivity, or order of sensitivity to the different metals tested, whether essential or non-essential.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…Despite the low number of tests carried out on species of echinodermatas other than L. variegatus, the values obtained are within the range of variation and/or of the same order of magnitude observed by other authors who investigated the sensitivity of A. lixula LAITANO, 2002;MÁXIMO et al, 2008;RESGALLA et al, 2012), E. lucunter (RUMBOLD; SNEDAKER, 1997; RESGALLA JÚNIOR; LAITANO, 2002) and the sand dollar Mellita quinquiesperforata (LAITANO et al, 2008), which validate the results obtained in this work. On the basis of this, it was suggested that the different species tested have similar sensitivity, or order of sensitivity to the different metals tested, whether essential or non-essential.…”
Section: Discussionsupporting
confidence: 68%
“…This downward trend of differences in sensitivity in Echinodermata has already been highlighted by other studies in Brazil involving different test organisms (RESGALLA JÚNIOR; LAITANO, 2002;MÁXIMO et al, 2008;LAITANO et al, 2008). Associated with this, HIS et al (1999), in studies on tests with molluscs, also emphasize that species with distinct ecological and phylogenetic characteristics may respond similarly to some toxicants.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Nitokra sp showed more sensitivity to potassium dichromate compared to freshwater fish such as Piracactus mesopotamicus (pacu); Hyphessobrycon eques (weed-thick) and Phalloceros. caudimaculttus (guarú) (Cruz et al, 2008), and less sensitivity than embryos of echinoids such as Mellita quinquesperforata, Arbacia lixula and Lytechinus variegatus, frequently used in aquatic tests in studies developed by Resgalla & Laitano (2002); Laitano et al (2008) and Maximo et al (2008), respectively (Table 4).…”
Section: Resultsmentioning
confidence: 99%
“…This limitation is associated with the fact that the toxicity of this form of nitrogen could lead to false results when using very sensitive test organisms. Embryos and larvae of sea urchins have a high sensitivity to NH 3 in a concentration of 0.050 mg L -1 as a tolerance limit for the development of organisms (NBR/ABNT, 2020 and Máximo et al, 2008). Likewise, sperm used in sea urchin fertilization assays can be twice as resistant to unionized ammonia (LC 50 = 0.169 mg L -1 ) (Lee et al, 2013).…”
Section: Discussionmentioning
confidence: 99%